Translational regulation of human erythropoietin (EPO) by an upstream open reading frame (uORF) and its impact on myocardial ischemia - Romão, Luísa (2025)
Functional upstream open reading frames (uORFs) are cis-acting regulatory elements of gene expression located upstream of the main initiation codon [usually, located in the 5’ untranslated region (5’UTR)] that repress mRNA translation (protein synthesis) of the main ORF in physiological conditions. Under stress conditions, uORFs alleviate their repressive effect, as a response to the cellular environmental change. About half of the human mRNAs (mainly, transcripts encoding growth factors or hormones) present uORFs. However, for the vast majority of the cases, the principles by which uORFs participate in translational control are still poorly understood. The fact that mutations that introduce or disrupt a uORF can cause human diseases illustrates their role in translational regulation. Identifying when and how they function is essential to understand the etiology of many human disease-associated uORFs and establish their therapies. In its classical hormonal role, human erythropoietin (EPO) is a glycoprotein synthesized and released mainly from the kidney, which has a key role in hematopoiesis. However, recent studies have revealed that EPO is a multifunctional molecule produced and utilized by many tissues (e.g. brain, heart and liver) that rapidly responds to different cell stress stimuli and tissue injuries. For example, EPO is upregulated in the brain and heart after injury and shows a tissue protective effect due to its antiapoptotic, anti-inflammatory, antioxidative and angiogenetic properties. Thus, it has the potential to be used as a therapeutic target/strategy for the treatment of several human disorders, including ischemic injuries in brain or heart. Understanding the EPO translational control mechanisms will be valuable in the determination of these therapies. EPO is a 165 amino acid protein encoded by 1340 nucleotides (nts) transcript (NM_000799) that presents a 5’UTR with 181 nts containing a uORF with 14 codons that terminates 22 nts upstream of the EPO initiation codon. However, the role of this uORF is unknown. The aim of this project was to study the role of the EPO uORF in its translational control.